Gamification Equilibrium: The Fulcrum for Balanced Intrinsic Motivation and Extrinsic Rewards in Learning Systems - Dah John; Norhayati Hussin; Muhamad Khairulnizam Zaini; Divine Senanu Ametefe; Abdulmalik Adozuka Aliu; Aziz Caliskan (Serious Games Society, 2023)
In this study we developed a concept for balancing extrinsic rewards and intrinsic motivation in gamified learning systems through the laws of levers. Although empirical findings around gamification studies remain largely inconclusive, it is still the go-to place for many who seek to improve motivation and engagement. The phenomenon uses game design elements and game principles to create better user experience on a system or activity. With the widespread of gamification across and beyond IS, the field of education and learning is one that has embraced it solemnly. Nevertheless, there is little to no consensus amongst researchers as to how to effectively apply it, and benefit from it. As such, the concept is yet entrenched; although popular. Hence, along the concept development, this study set out to review the setbacks of gamification in recent times, primarily focusing on the current inconsistencies of empirical outcomes and how these challenges can be mitigated. We discovered that the overreliance of developers on narrow models is a culprit for failed gamification. Shallow gamification design which centres around the so-called "BPL gamification" is a source of failure, as it has become a copy-and-paste cliché, rather than a deliberate contextual design. Inordinate selection, and application of game elements to a system/activity is toppling gamification too. This was found to also create imbalances in both extrinsic and intrinsic motivation thereby leading to what is known as "Overjustification effect", which is a big killer of gamification today.